Justice for the Parties to the Standard Agreement Relating to the Freedom Contract Principle - Prihandini, Nadia Aurynnisa; Priyono , Ery Agus (Alauddin Law Development Journal, 2024)
This research investigates the considerations necessary for creating a fair standard contract and implementing the principle of freedom of contract. A standard contract, typically drafted by one party with predetermined terms, is crucial in commercial transactions. Despite the principle of freedom of contract, ensuring fairness for all parties involved remains a challenge. The method employed is normative juridical research, utilizing secondary data sources. The findings showed that the standard contracts may not violate the principle of freedom of contract outlined in Article 1320 and Article 1338 of the Civil Code, conflicts may arise, particularly due to restrictive clauses like exoneration clauses. Parties have the right to review the contract and accept or reject its terms. However, disparities persist in standard contract formation, highlighting the need for further examination of their fairness and compliance with legal principles